2D BASIN MODELLING IN THE EASTERN VARISCAN FOLD BELT (CZECH REPUBLIC): INFLUENCE OF THRUSTING ON PATTERNS OF THERMAL MATURATION. (13th March 2018) - Jirman, P.; Geršlová, E.; Kalvoda, J.; Melichar, R.
Abstract : This study evaluates the geothermal history of Palaeozoic sedimentary rocks from the easternmost part of the Variscan external zone in the NE Czech Republic. The objective was to investigate the geothermal history of pre‐Variscan Palaeozoic carbonates in the study area, and to assess its relationship with that of the overlying Variscan flysch. In the study area, the Palaeozoic succession occurs at the surface or is overlain by Miocene sediments of the Carpathian Foredeep. Palaeozoic nappes and the main Variscan overthrust have been documented in the subsurface at the deep Potštát‐1borehole. Vitrinite reflectance measurements on 38 samples from the Potštát‐1 well and 19 samples from nearby surface outcrops and shallow boreholes were available. A 2D thermal model was created using PetroMod and the thermal maturity evolution was modelled by EASY%Ro. The thermal model was constructed based on interpretations of two NW‐SE seismic profiles (lines 5/83 and 5/84) oriented perpendicular to the main Variscan thrusts. The results were calibrated using measured vitrinite reflectance and were adjusted with 1D models from three shallow boreholes. At the Potštát‐1 borehole, modelled maximum palaeo‐temperatures of the Variscan flysch (Moravice Formation) ranged from 310°C at a depth of 7.3 km (the top of the preserved succession) to 395°C at the base of the succession, resulting in thermal maturities of >4%Rr . Peak maturation occurred prior to the end of Variscan thrusting. Modelling suggests that the basal heat flow for these thrust units reached a maximum value of 63 mW/m 2 at 325 Ma. In addition, the modelling suggests that the maturity of the Palaeozoic carbonates was controlled by the thickness of the overlying Variscan flysch nappes. Maximum palaeo‐temperatures for the Palaeozoic carbonates ranged from 265°C at the top of the interval (at a depth of 7.1 km) to 290°C at the base, resulting in a maturity of 3.8 to >4%Rr which is within the dry gas window. The study suggests that basal heat flows in the original (pre‐thrust) Early Carboniferous sedimentary basin were slightly higher than those in the post‐thrust location for the Variscan flysch nappes. This should be taken into account when evaluating the petroleum system in the South Moravian oil province (SW Czech Republic) where a complete sedimentary sequence has not been preserved.